Information, cities and disaster mitigation social media use by cities in Metro Manila - Delos Santos, Maricris B.; Alampay, Erwin Gaspar A. (2015)
Given the recent disasters that struck the Philippines in the past few years such as Typhoons Yolanda (Haiyan, 2013) and Glenda (Rammasun, mid-2014), the need for awareness and alertness on local conditions and updates of Filipino citizens has been more pronounced. This trend was evident in social media, which is now seen as a new conduit for more effective information dissemination. This study looks at how Metro Manila city governments use and manage social media, specifically Facebook and Twitter, for disaster risk mitigation and management (DRRM). The study found that there is no uniformity in how local government units (LGUs) manage their social media for DRRM. For one, different LGU offices create and manage social media accounts. Most are managed by public information offices (PIO), and a few are being managed by the DRRM office. There is a protocol in creating and managing official social media accounts of LGUs. In terms of content of the social media posts, information mostly included typhoon warnings, flood warnings and traffic advisories. Recommendations are drawn from the findings of the study to effectively maximize social media for DRRM.
Keywords: Crisis communication; Disasters -- Social aspects; Emergency communication systems -- Technological innovations; Hazard mitigation; Online social networks; Social media